Analysis of Historical Worker Exposures to Respirable Dust from Talc Mining and Milling Operations in Vermont. Issue 4 (12th February 2020) - Rossner, Alan; Williams, Pamela R D; Mellas-Hulett, Elayna; Rahman, Mohammad Arifur
Abstract: Objectives: Talc is mined and milled throughout the world for use in a variety of industrial and consumer products. Although prior studies have evaluated workplace exposures or health effects from talc operations, the primary emphasis of these investigations has been on certain mineral contaminants (e.g. crystalline silica and asbestos) rather than talc itself. The purpose of this analysis is to evaluate historical worker exposures to respirable dust (as a measure of talc exposures) in the Vermont talc mines and mills, which involved a relatively pure form of talc (i.e. no asbestos and <0.25% or <1% crystalline silica). Methods: Respirable dust sampling data collected for workers in the Vermont mines and mills, which have not been previously published, were obtained from both mining company records and Mine Safety and Health Administration (MSHA) inspections. Because of differences in sampling design, the company and MSHA data were analyzed and reported separately. Overall, nearly 700 respirable dust samples collected for 44 job categories at 7 site locations over an approximate 30-year period were analyzed. Results: Average respirable dust concentrations were found to exceed occupational exposure limits (OELs) in the United States and other countries for several job categories and site locations. Regardless of data source, the highest observed exposures were for mining jobs involving the operation of heavy equipment to break up, move, or load raw ore from the mines and milling or shipping jobs involving the crushing of raw ore, cleaning and drying of processed talc, and bagging and packaging of the final talc product. When analyzing the company data, the arithmetic mean respirable dust concentration was 2.73 mg m −3 for Muckerman at Hammondsville Mine, 3.18 mg m −3 for dosco operator at Ludlow mines, 1.35 mg m −3 for crusher operator at Gassetts Mill, 2.4 mg m −3 for palletizer at West Windsor Mill, and 2.68 mg m −3 for bagging operator at Columbia Shipping Center. When analyzing the MSHA data, the arithmetic mean respirable dust concentration was 3.5 mg m −3 for kiln/dryer operator at Hammondsville Mine, 1.27 mg m −3 for driller at Ludlow mines, 3.69 mg m −3 for ball mill operator at Columbia mill, 3.02 mg m −3 for flotation operator at West Windsor Mill, and 3.24 mg m −3 for bagging operator at Columbia Shipping Center. Worker exposures were found to decline over time for many, but not all, jobs. Conclusions: Our findings highlight potential high-risk jobs that might benefit from additional exposure control strategies at current or future talc manufacturing sites. The respirable dust measurements summarized here may also be used to reconstruct historical worker exposures at the Vermont sites or aid in subsequent epidemiology studies of this cohort focused on malignant or non-malignant respiratory disease.